Penerapan Manajemen Layanan Bimbingan dan Konseling dalam Upaya Meningkatkan Mutu Belajar Siswa - Machfudz Machfudz (Kuras Institute, 2022)
Equity and access to education in Indonesia show that it is still far from expectations. In maximizing students' potential, guidance and counseling service management is needed significantly to improve the quality of learning in the hope of producing quality learning achievements by implementing planning, organizing, staffing, leading, and controlling. This study aims to review the application of guidance and counseling service management to improve the quality of student learning. This study uses a literature study method sourced from trusted books, journals, and articles relating to the management of guidance and counseling services to improve the quality of student learning. The study results indicate that the management of guidance and counseling needs to be done to improve the quality of student learning. Therefore, it is necessary to have a preparation or programming before doing counseling.